A multistage oral delivery system of PTX for improving oral bioavailability and enhancing anticancer efficacy. (1st February 2021) - Zhao, Ting; Zhou, Hongli; Wu, Wanyan; Song, Xu; Gong, Tao
Abstract: Objective: Bromotetrandrine (W198) was reported as a P-glycoprotein (P-gp) inhibitor. We aimed to prepare oral W198 micelles following by paclitaxel (PTX) micelles (W198/PTX micelles) to improve the clinical application of PTX. Significance: The poor water solubility, intestinal permeability, and multidrug resistance (MDR) of PTX can be improved in the multistage oral delivery system. Methods: The novel W198/PTX oral micelles were developed by water-bath ultrasound method and were evaluated in vivo and in vitro in 4T1 orthotopic tumor-bearing mice model. Results: PTX micelles and W198 micelles were prepared to be round and uniform. W198 micelles pre-administrated group showed higher cellular uptake efficiency of PTX on Caco-2 cells and more prominent cytotoxicity compared with W198-untreated group on 4T1 cells. The oral bioavailability of W198/PTX micelles group was nearly 5.7-folds higher than the PTX micelles only group. In addition, W198/PTX micelles showed enhanced anticancer efficacy. Conclusions: We established a multistage oral delivery system to improve oral bioavailability and anticancer efficacy of PTX.